Cinderella (Parragon Books Ltd, 2014)
When all the ladies in the kingdom are invited to a royal ball,Cinderella desperately want to go-but she has nothing to wear and no time to get ready. Will Cinderella's dreams come true?...
Keywords: Fairytales